Evaluation of competencies of public extension officers on the use of climate-smart agriculture strategies by smallholder farmers in Capricorn District Municipality-Limpopo Province in South Africa - Chaza, Nomzamo (My University, 2024)
Globally, the significance of extension officers in promoting the adoption of Climate Smart Agriculture (CSA) among small-scale farmers is increasing. This study assessed the competencies of public extension officers in implementing CSA strategies in smallholder farming within Limpopo province. This evaluation is vital for ensuring an ongoing professional development of public extension officers, enabling them to effectively navigate evolving CSA strategies and deliver comprehensive advisory services to farmers. The study's objectives were: (i) to describe the socio-economic characteristics of the extension agents, (ii)to determine the Knowledge, Attitude, Perception (KAP) and understanding the level held by extension agents towards the use of CSA, (iii) to identify factors that influence access to information and technology for climate smart agricultural users. To evaluate competencies of extension officers in implementing climate-smart agriculture, a quantitative research design was employed. Data was collected through a structured questionnaire administered to 80 out of the 85 officers in the area using convenience sampling. The analysis of the data was conducted using descriptive statistics, which provided valuable insights the demographic and professional characteristics of the respondents. The study's findings revealed several key demographic and professional characteristics of the respondents. The most prevalent age group was 46 years and older. In terms of gender distribution, most respondents were female (54.9%), followed by males (45.1%). The predominant marital status among respondents was married (50.7%), and a considerable proportion holds a degree as their highest education level (46.5%). The mean indicator score was notably higher for knowledge (0.6928). This implied that extension officers in the study area exhibit a substantial level of knowledge regarding climate-smart strategies. Despite the positive findings, the study identified challenges faced by extension officers in enhancing their knowledge of climate-smart adaptation strategies. These challenges include three recurring factors, which consistently influenced access to information and technology for users engaged in climate-smart agriculture. The influential predictors affecting access to information and technology in Capricorn district were three Coping and Adaptation Strategies, Acquisition of Knowledge, and lastly Computer and ICT Skills. The study proposed recommendations based on its findings, aimed at fostering collaboration among v stakeholders for the efficiency and longevity of agricultural extension services in Capricorn district. Recommendations for extension officers include active engagement in continuous learning, participation in community outreach programs, embracing innovation, and acting as mentors to junior colleagues. Researchers are encouraged to collaborate closely with extension officers, support innovation adoption, and contribute to the development of training programs. Educational institutions should update curricula, develop practical training programs, and establish continuous professional development systems. The Department of Agriculture is advised to strategically allocate resources, advocate for policies supporting CSA practices, establish monitoring and evaluation frameworks, and facilitate collaboration among stakeholders.
Thesis (M. Agriculture (Agricultural Management)) -- University of Limpopo, 2024
Keywords: Climate Smart Agriculture; KAP; Climate-smart strategies; Crops and climate; Agricultural administration -- South Africa -- Limpopo; Irrigation farming -- Climatic factors; Farms, Small -- South Africa -- Limpopo; Farmers -- South Africa -- Limpopo